Effects of system benzylaminopurine-adenine sulphate in combination with naphthalene acetic on in vitro regeneration and proliferation of pineapple (Ananas comosus (L.) Mill var. comosus). - AGBIDINOUKOUN, ARNAUD (My University, 2018)
In vitro micropropagation is now used in the production of healthy and homogenous pineapple planting materials. In order to increase the in vitro proliferation of pineapple, the synergetic effect of adenine sulphate (AdS) and benzylaminopurine (BAP) in presence or not of naphthalene acetic acid (NAA) was evaluated. Median axillary buds of crowns bursted 6 to 8 weeks old were cultured on Murashige and Skoog medium supplemented with BAP (0, 1 and 2 mg/l), NAA (0 and 0.5 mg/l) with or without AdS (40 mg/l). Five buds per treatment with four replicates were used. The addition of BAP to the medium stimulated regeneration (65 to 82%) and multiplication (3.04 to 6.13 plantlets/explant) which were further enhanced by the addition of NAA (98%; 6.42 plantlets/ explant). AdS highly stimulated proliferation in presence of 2 mg/l BAP and NAA (14.96 plantlets/explant), plantlet mass (1.143g) but limited plantlet growth in height which was more induced in the absence of regulators (4.88 cm) and with AdS alone (5.63 cm). Thus, BAP is necessary for the proliferation of pineapple and the addition of 0.5 mg/l NAA to 2 mg/l BAP and 40 mg/l AdS optimizes the multiplication and growth parameters of pineapple plantlets. These results allow the mass propagation of pineapple’s homogeneous healthy planting materials.
Keywords: Pineapple; micropropagation; adenine sulphate; benzylaminopurine; naphthalene acetic acid; shoots.